Another (Internal) Epineurium: Beyond the Anatomical Barriers of Nerves. Issue 2 (19th August 2019) - Reina, Miguel A.; Boezaart, André P.; Tubbs, R. Shane; Zasimovich, Yury; Fernández‐Domínguez, Manuel; Fernández, Paloma; Sala‐Blanch, Xavier
Abstract : The epineurium has been accepted as the outer anatomical barrier of the peripheral nerves. Our objective was to characterize the microanatomy of the layers surrounding nerves using different tissue‐specific staining methods. Two hundred forty‐two cross sections of human sciatic and median nerves, and brachial plexuses of eight fresh unembalmed cadavers, were examined. The samples were fixed in formaldehyde solution and stained with hematoxylin–eosin, Masson's trichrome, or epithelial membrane antigen under standard conditions. Because epithelial membrane antigen only stains the perineurium, we demonstrated using hematoxylin–eosin and Masson's trichrome that there were different collagen layers inside and outside the nerves. All fascicles had a collagen layer that surrounded the perineurium and were in close contact with it, with no adipose tissue between them. Unlike the perineurium, this layer, an "internal epineurium, " contained no cells, and it surrounded one or a small group of fascicles. Bundling these fascicles or small groups of fascicles together was the true epineurium, and between the true and internal epineurium, we consistently found an adipose‐containing compartment. More proximal to this, the tibial and common peroneal nerves were bundled together by another collagen layer, the circumneurium, which also had a fat‐cell‐containing compartment deep to it. There were scattered collagen fibers among the adipocytes. Using tissue‐specific staining, we were able to demonstrate a collagen layer, the "internal epineurium." Outside the nerves, we identified several fat‐containing concentric compartments. Those compartments were limited by collagen fiber layers that were also similar to the epineurium. Clin. Anat. 33:199–206, 2020. © 2019 Wiley Periodicals, Inc.